1994
DOI: 10.1677/joe.0.1410163
|View full text |Cite
|
Sign up to set email alerts
|

Opioid peptide and α-adrenoceptor pathways in the regulation of the pituitary-adrenal axis in man

Abstract: Opioid peptides are well established as potent inhibitors of the pituitary-adrenal axis, while alpha 1-adrenoceptor drugs have recently been shown to stimulate this axis: both classes of agents appear to work principally above the level of the pituitary, most probable directly on the hypothalamus. There is also evidence that these drugs interact in their control of pituitary-adrenal function, although the specific hypothalamic releasing hormone involved has remained unclear. We have therefore carried out a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 0 publications
4
31
0
1
Order By: Relevance
“…One study has shown a methoxamine (a1-adrenergic agonist)-induced increase of CRH-stimulated ACTH and subsequent serum cortisol increase which are compatible with our results (25). In another experiment, the unspecific a1,2-adrenergic antagonist, phentolamine, had no influence on CRHstimulated ACTH and cortisol levels (24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One study has shown a methoxamine (a1-adrenergic agonist)-induced increase of CRH-stimulated ACTH and subsequent serum cortisol increase which are compatible with our results (25). In another experiment, the unspecific a1,2-adrenergic antagonist, phentolamine, had no influence on CRHstimulated ACTH and cortisol levels (24).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to two earlier studies with propranolol and CRH injection (24,25) or propranolol and hypoglycemia (e.g. 24,26,27), this study extended the earlier view by consideration of molar hormone ratios such as cortisol/adrenocorticotropin (ACTH), cortisol/17-hydroxyprogesterone (17OHP), cortisol/DHEA, and DHEAS/DHEA.…”
Section: Introductionmentioning
confidence: 79%
“…In normal subjects, the infusion of naloxone elevates plasma ACTH and cortisol but only if given in high doses, above 10 -15 mg (1,3,32,36,39,40). In agreement with these data, we found that the infusion of approximately 9 mg naloxone, over 6 1 ⁄2 h, had no effect on plasma ACTH levels during normocortisolism.…”
Section: Discussionsupporting
confidence: 87%
“…Opioid antagonist administration blocks the tonic opioid inhibition of HPA axis activity, thereby resulting in release of POMC-derived hormones in the pituitary and cortisol from the adrenal gland. Indeed, numerous studies have demonstrated acute increases in adrenocorticotropin (ACTH) and cortisol levels in man after intravenous infusion of the opioid antagonists naloxone (Cohen et al 1983;Conaglen et al 1985;Delitala et al 1994;Naber et al 1981;Martin del Campo et al 1994;Morley et al 1980;Schluger et al 1998;Volavka et al 1979a) and nalmefene . However, few studies have examined acute neuroendocrine response to the opioid antagonist naltrexone, which, in contrast to naloxone and nalmefene, is not available for intravenous administration.…”
mentioning
confidence: 99%